El Excentrico, 1976-12-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, CA; Garcia Printing, 2024)
December 5, 1976 [5 de diciembre de 1976]. Ano 27, No 16. Cover contains a photo of Daniel G. Saldana, the former president of the Los Amigos Lions Club. The headline reads, "A Tribute to Daniel G. Daldana."